Modern and Contemporary Architecture Between Western and Arab Countries: A Review of Derivative Synonyms - Sharara, Hussein (European Scientific Journal, ESJ, 2022)
The most common approaches to contemporary architecture are described as ’modern’, yet the terms ’modern’ and ’contemporary’ possess different contextual weights, resulting in a difference in terminological synonymy. This research examines the phenomenon that emerged in the late twentieth century, processes its conflicts, and describes several interrelated implications for understanding modernity and contemporariness. This research discusses the confusion between contemporary and modernist architectural representation by analyzing Western and Arab visions. Furthermore, it explores the study with inductive logic that takes an analytical turn to analyze, compare, and explore the real causes of the problem. The research also aims to analyze the impact of modernism, the semantic evolution of ’modernity’, and our arrival to the contemporary, considering neoliberalism and globalism. The research concluded that separating the idiomatic language from the architectural language is necessary. Furthermore, it found that contemporary ended as an architectural style and continued as a cultural movement.